2017
DOI: 10.1177/1362168817739650
|View full text |Cite
|
Sign up to set email alerts
|

L1–L2 differences in the L2 classroom: Anticipating Anglophone learners’ difficulties with French pronoun interpretation

Abstract: In this article, we address the issue of targeted instruction on interpretive contrasts between native and second-language grammatical meanings. Such mismatches are predicted to create challenges for learners. We illustrate this with French and English pronouns. In French, clitic pronouns ( le, la) point to human as well as inanimate referents, while English pronouns distinguish between human ( him, her) and inanimate ( it) referents. While other grammatical differences between English and French pronouns are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…A recent study by Wu, Li, and Qin (in press) indicated that the Mandarin plural pronoun tamén (counterpart of the English plural they ) functioning as a singular pronoun is not acceptable for Mandarin native speakers. Such a discrepancy between the two languages has been found to be an important source of difficulty in L2 learning, particularly when it comes to the restructuring of existing knowledge for the plural feature of they [−PLURAL] and the adaptation to the sociocultural norms of the target language ( Ellis, 2016 ; Shimanskaya and Slabakova, 2017 ). To overcome such a difficulty, Chinese EFL learners are likely to require positive evidence of the correct use of the singular they from their language input ( Gabriele, 2009 ), yet such input is rare in Chinese classroom settings ( Xie, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Wu, Li, and Qin (in press) indicated that the Mandarin plural pronoun tamén (counterpart of the English plural they ) functioning as a singular pronoun is not acceptable for Mandarin native speakers. Such a discrepancy between the two languages has been found to be an important source of difficulty in L2 learning, particularly when it comes to the restructuring of existing knowledge for the plural feature of they [−PLURAL] and the adaptation to the sociocultural norms of the target language ( Ellis, 2016 ; Shimanskaya and Slabakova, 2017 ). To overcome such a difficulty, Chinese EFL learners are likely to require positive evidence of the correct use of the singular they from their language input ( Gabriele, 2009 ), yet such input is rare in Chinese classroom settings ( Xie, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The papers in this volume can be divided into two sets: those that report on a teaching intervention study that aims to incorporate linguistic description from generative linguistic research into grammar instruction (Hirakawa et al, 2018;Lopez, 2017;Umeda et al, 2017) and those that combine experimental L2 acquisition work with pedagogically oriented research, including a survey of the presentation of linguistic properties in textbooks (Gil et al, 2017), a survey of language teacher views and investigation of classroom input (Leal & Slabakova, 2017), and exploration of materials development (Shimanskaya & Slabakova, 2017).…”
Section: Introduction To Papersmentioning
confidence: 99%
“…For example, in relation to the English articles a and the, the paper by Lopez (2017) highlights the meanings of definite noun phrases and specific noun phrases, with a view to helping the L2 student realize that there is a difference between these two meanings, and that only one of them (definiteness) is captured in a and the. Or, in teaching French, Shimanskaya and Slabakova (2017) consider the utility of emphasizing that gendered clitic pronouns stand for inanimate things, not just for people, in contrast to gendered pronons in English.…”
mentioning
confidence: 99%
See 1 more Smart Citation